Common microscopic origin of the phase transitions in Ta2NiS5 and the excitonic insulator candidate Ta2NiSe5 - Windgätter, Lukas; Rösner, Malte; Mazza, Giacomo; Hübener, Hannes; Georges, Antoine; Millis, Andrew J.; Latini, Simone; Rubio, Angel (npj computational materials, 2021)
The structural phase transition in Ta 2 NiSe 5 has been envisioned as driven by the formation of an excitonic insulating phase. However, the role of structural and electronic instabilities on crystal symmetry breaking has yet to be disentangled. Meanwhile, the phase transition in its complementary material Ta 2 NiS 5 does not show any experimental hints of an excitonic insulating phase. We present a microscopic investigation of the electronic and phononic effects involved in the structural phase transition in Ta 2 NiSe 5 and Ta 2 NiS 5 using extensive first-principles calculations. In both materials the crystal symmetries are broken by phonon instabilities, which in turn lead to changes in the electronic bandstructure also observed in the experiment. A total energy landscape analysis shows no tendency towards a purely electronic instability and we find that a sizeable lattice distortion is needed to open a bandgap. We conclude that an excitonic instability is not needed to explain the phase transition in both Ta 2 NiSe 5 and Ta 2 NiS 5 .